2008
DOI: 10.1080/10739680802107447
|View full text |Cite
|
Sign up to set email alerts
|

RBC Aggregation: More Important than RBC Adhesion to Endothelial Cells as a Determinant of In Vivo Blood Flow in Health and Disease

Abstract: Although the shear-dependent and reversible phenomenon of red blood cell (RBC) aggregation has been studied for decades, its role as a determinant of in vivo blood flow in both health and disease has not yet been fully documented. In this brief review, we present compelling arguments, supported by literature evidence, that in vivo flow dynamics are more affected by RBC aggregation than by RBC adhesion to endothelial cells (ECs). A companion article (i.e., a "counter-point") published in this issue of the journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 36 publications
4
67
1
1
Order By: Relevance
“…20 This may increase flow resistance, promote arteriovenous shunts and disturb microcirculation at the entry of the pulmonary capillaries where RBC aggregates need to be fully dispersed before they can enter and negotiate small capillaries to promote adequate gas exchange between the lungs and RBC. 46 A major limitation of the present study is the absence of a healthy control group. Campbell et al 6 showed that 52% of sickle patients (SC, SS, Sb thalassemia, SO Arab and other genotypes) and 24% of healthy controls (matched for age and ethnicity) had resting hemoglobin oxygen saturation of less than 99%, and 9% of patients versus no controls had resting hemoglobin oxygen saturation level of less than 95%.…”
Section: Discussionmentioning
confidence: 99%
“…20 This may increase flow resistance, promote arteriovenous shunts and disturb microcirculation at the entry of the pulmonary capillaries where RBC aggregates need to be fully dispersed before they can enter and negotiate small capillaries to promote adequate gas exchange between the lungs and RBC. 46 A major limitation of the present study is the absence of a healthy control group. Campbell et al 6 showed that 52% of sickle patients (SC, SS, Sb thalassemia, SO Arab and other genotypes) and 24% of healthy controls (matched for age and ethnicity) had resting hemoglobin oxygen saturation of less than 99%, and 9% of patients versus no controls had resting hemoglobin oxygen saturation level of less than 95%.…”
Section: Discussionmentioning
confidence: 99%
“…25 This increase of the required shear forces might have important physiological consequences, especially at the microcirculatory level, since RBC are only able to pass through small capillaries as single cells. 5 However, since γmin for SCA and SCC patients were similar, differences of blood viscosity and RBC deformability between the two groups probably play a role in their unequal clinical severity. 26 Although the forces required to disperse preformed RBC aggregates are elevated in SCA and SCC subjects, the extent of aggregation at stasis (i.e., AI) was lower than control in both groups; this finding contrasts with results obtained by Obiefuna et al 27 on SCA patients but is consistent with results obtained by Chien et al 2 The reasons for the discordant results for aggregation at stasis remain unknown, but may be due to different experimental methods: in the current study defined preshearing of blood samples to disperse pre-existing aggregates was employed whereas it was not part of the microscopic method used by Obiefuna et al 27 Note that the present results indicate that time for formation of RBC aggregates is increased in SCA and SCC patients ( Table 3), meaning that the formation of branched 3-dimension aggregates is slower in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although the forces required to disperse preformed RBC aggregates are elevated in SCA and SCC subjects, the extent of aggregation at stasis (i.e., AI) was lower than control in both groups; this finding contrasts with results obtained by Obiefuna et al 27 on SCA patients but is consistent with results obtained by Chien et al 2 The reasons for the discordant results for aggregation at stasis remain unknown, but may be due to different experimental methods: in the current study defined preshearing of blood samples to disperse pre-existing aggregates was employed whereas it was not part of the microscopic method used by Obiefuna et al 27 Note that the present results indicate that time for formation of RBC aggregates is increased in SCA and SCC patients ( Table 3), meaning that the formation of branched 3-dimension aggregates is slower in these subjects. The effects of RBC aggregation on in vivo flow dynamics and flow resistance are complex 5,28 and further studies are warranted to better understand the association between RBC aggregation parameters and the severity of sickle cell disease. Although some hemorheological parameters differed between SCC and SCA patients, both have markedly reduced and essentially identical HVR levels at all shear rates ( Figure 1); our calculated mean HVR values are consistent with the range reported by Serjeant et al 29 Thus the oxygen transport effectiveness of blood in SCA and SCC subjects is lower than in controls, a finding also seen in other disease states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations